2013
DOI: 10.1007/s40268-013-0014-8
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Coadministered Guanfacine Extended Release and Lisdexamfetamine Dimesylate

Abstract: BackgroundIn clinical practice, α2-adrenoceptor agonists have been adjunctively administered with psychostimulants for the treatment of attention-deficit/hyperactivity disorder (ADHD). Two studies have examined the adjunctive use of guanfacine extended release (GXR, Intuniv®; Shire Development LLC, Wayne, PA, USA) with psychostimulants in children and adolescents with a suboptimal response to psychostimulant treatment. However, the potential for pharmacokinetic drug–drug interactions (DDIs) between GXR and lis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…Moreover, no unique TEAE emerged from GXR adjunctive to a long-acting psychostimulant. 26,50 This is consistent with findings from studies conducted in healthy adults showing that no unique TEAEs were observed with coadministration of GXR and MPH 47 or lisdexamfetamine 48 compared with either treatment alone.…”
Section: Safety and Tolerability Of Guanfacinesupporting
confidence: 88%
See 1 more Smart Citation
“…Moreover, no unique TEAE emerged from GXR adjunctive to a long-acting psychostimulant. 26,50 This is consistent with findings from studies conducted in healthy adults showing that no unique TEAEs were observed with coadministration of GXR and MPH 47 or lisdexamfetamine 48 compared with either treatment alone.…”
Section: Safety and Tolerability Of Guanfacinesupporting
confidence: 88%
“…45 In addition, when guanfacine and valproic acid are administered simultaneously, plasma valproate levels may rise significantly. 46 However, two small openlabel studies conducted with healthy adults revealed that coadministration of GXR and MPH 47 or lisdexamfetamine 48 did not result in significant pharmacokinetic drug-drug interactions.…”
mentioning
confidence: 99%
“…The method developed for the three matrices was validated and was also successfully applied to assess real samples, showing for the first time the detection of LDX in oral fluid. ; Roesch et al, 2013;Rowley et al, 2012). Therefore, the aim of this study is to describe the development and validation of an LC-MS/MS method for the simultaneous quantification of LDX and its main biotransformation product AMPH in human oral fluid, plasma and urine.…”
mentioning
confidence: 99%
“… 45 In addition, when guanfacine and valproic acid are administered simultaneously, plasma valproate levels may rise significantly. 46 However, two small open-label studies conducted with healthy adults revealed that coadministration of GXR and MPH 47 or lisdexamfetamine 48 did not result in significant pharmacokinetic drug–drug interactions.…”
Section: Pharmacology Of Guanfacinementioning
confidence: 99%